Faktor-Faktor Yang Mempengaruhi Keberhasilan Implementasi Sistem Informasi Manajemen Rumah Sakit Literature Review - Denisistya Krisworo; Efri Tri Ardianto; Feby Erawantini; Mochammad Choirur Roziqin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
According to the Regulation of Health Minister of the Republic Indonesia Number 82 of 2013 concerning Hospital Management Information, it is that every hospital is required to implement a Hospital Management Information System (SIMRS). However, according to a literature study conducted by researchers in the implementation of SIMRS, there are still many obstacles. With the implementation of SIMRS that is not good, it will have an impact on service to patients so that influences the success of the Hospital Management Information System Implementation. This research method is a literature review using 20 articles published in 2011-2021 on Google Scholar and Pubmed. The result of the factor that affected the success of the implementation of the hospital system, 30% stated that hardware, 55% state that software, 25% stated that procedures, 45% stated that basis data, 25% stated that networks and 75% stated that people component affected the success of system implementation. The very important influence of the successful implementation of the hospital Management information system is the people’s factors. So that in implementing SIMRS, we must pay attention to these factors, especially people factors in order to achieve the success of SIMRS implementation.